THE EFFECTIVENESS OF THERAPEUTIC COMMUNICATION BY DA'I IN REDUCING PSYCHOLOGICAL DISORDERS AMONG CONVERTS TO ISLAM: A Case Study at The Yayasan Pembinaan Mualaf Al Muhajirin - Rm, Sulaiman; Zainun; Cut Metia (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This study aims to analyze the psychological disorders experienced by converts (mualaf) at Yayasan Pembinaan Mualaf Al Muhajirin, the therapeutic communication employed by Dai in alleviating these disorders, and the implementation of therapeutic communication by Dai in reducing psychological distress among converts at Yayasan Pembinaan Mualaf Al Muhajirin. This research uses a descriptive qualitative approach with a case study method. Data were obtained through in-depth interviews with Dai and converts, field observations, and documentation. Informants were purposively selected from among the Dai of the foundation and the guided converts who had undergone the mentoring process. The results of the study indicate that converts at Yayasan Pembinaan Mualaf Al Muhajirin experience psychological disorders such as severe stress, social anxiety, overthinking, feelings of guilt, and inner conflict due to family rejection and identity crises. Therapeutic communication by the Dai is carried out through an empathetic approach, active listening, trust-building, and spiritual empowerment. The forms of communication used include both verbal and nonverbal communication, with strong religious and emotional content. The implementation of this communication has proven effective in gradually alleviating psychological symptoms, although several obstacles such as time constraints and limited abilities of the Dai remain challenges. The conclusion of this study shows that the therapeutic communication by Dai is effective in helping the psychological recovery process of converts, provided there is consistency, empathy, and depth in interpersonal relationships.